A TOOL FOR A DYNAMIC ADAPTATION OF THE OBJECTIVES AT THE LEVELS OF EUROPEAN UNION, NATIONAL AND SECTORAL, UNDER SECTORAL AND ACROSS SECTORS - Speranţa-Liliana NEAGU (Challenges of the Knowledge Society, 2016)
Changing of paradigms and realities generated by the dynamism shaping of international relations and the reality, especially determines a necessity of rapid modernization objectives to adapt to new constructs strategies and rules (soft law, common law and customary law, on the other hand). Creating of the conditions to open a chapter of the EU accession, or preparation of the content of acts of delegation or implementation concomitant of provisions of the EU Commission, to achieve the interests of socio-political nations, integrated - must be based on targets set by decisions triangular (COM; PE; CONS3) and through the "six thinking hats"4" – Maltese psychologist Edward de Bono.5 I created a simple tool for adaptation of the EU, national, sectoral, cross-sectoral objectives comparative for adaptation at dynamic reality. I created a simple tool for adaptation of the EU, national, sectoral, cross-sectoral objectives comparative for adaptation at dynamic reality.